Development of a multivariate prediction pipeline for differential antipsychotic treatment response outcomes in a Mixed-Ancestry first-episode schizophrenia cohort using schizophrenia polygenic risk scores - Knupp, Julieanne (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.